PENGARUH BAURAN PROMOSI DAN HARGA TERHADAP KEPUTUSAN MENGINAP KONSUMEN DI HOTEL ASTON NIU MANOKWARI - Sanggenapa, Aksamina; Bopeng, Louis Soemadi; Usman, Sarah (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2023)
ABSTRACT The study aims to examine and analyze the effect of the promotional mix and price on the decision to stay at the Hotel Aston Niu Manokwari. Primary data were obtained from observation, interview, and questionnaires and secondary data consisted of room rates and number of visitors in August, September and October in Aston Niu Manokwari Hotel. Research using a questionnaire, the analytical method used is Multiple Linier Regression. The sampling technique uses simple random sampling. The sampling used is 98 respondents who are costumers who have stayed at Hotel Aston Niu Manokwari. The result of this study indicate that : (1) Promotional mix has no effect on the decision to stay at the Hotel Aston Niu Manokwari; (2) the price partially has a significant effect on the decision to stay at the Hotel Aston Niu Manokwari; (3) The promotional mix and the price together affect the decision to stay at the costumers at Aston Niu Manokwari Hotel. The price variable has the greatest influence on the promotional mix variable. Based on this, the researcher suggests that the hotel can pay attention to promotional items again through sales promotions, personal selling, and direct marketing.